A Gravity Model of Migration between ENC and EU - Raul Ramos; Jordi Surinach (Institute for the Study of Labor (IZA), 2013)
Due to ageing population and low birth rates, the European Union (EU) will need to import foreign labour in the next decades. In this context, the EU neighbouring countries (ENC) are the main countries of origin and transit of legal and illegal migration towards Europe. Their economic, cultural and historical links also make them an important potential source of labour force. The objective of this paper is to analyse past and future trends in ENC-EU bilateral migration relationships. With this aim, two different empirical analyses are carried out. First, we specify and estimate a gravity model for nearly 200 countries between 1960 and 2010; and, second, we focus on within EU-27 migration flows before and after the enlargement of the EU. Our results show a clear increase in migratory pressures from ENC to the EU in the near future, but South-South migration will also become more relevant.
Keywords: J11; J15; J61; C23; C53; 330; bilateral migration; EU neighbouring countries; gravity model; push and pull migration factors